Is Additional Schooling Worthless? Revising Zero Returns to Compulsory Schooling in Germany - Kamila Cygan-Rehm (Center for Economic Studies and ifo Institute (CESifo), 2018)
This study estimates the effect of compulsory schooling on earnings. For identification, I exploit a German reform that extended the duration of secondary schooling in the 1960s. I find that hourly wages increase by 6%-8% per additional year of schooling. This result challenges prior findings for Germany of zero returns to schooling, obtained by using the same survey data and reform. I show that the earlier estimates suffer from unconsidered institutional details. A complementary analysis using social security records confirms significant effects on earnings, but yields no effects on employment and take-up of public transfers.
Keywords: I21; I26; J31; 330